Association between anxiety and mortality in patients with coronary artery disease: A meta-analysis - Celano, Christopher M.; Millstein, Rachel A.; Bedoya, C. Andres; Healy, Brian C.; Roest, Annelieke M.; Huffman, Jeff C. (The American heart journal, 2015)
Depression and anxiety are common in patients with coronary artery disease (CAD). Although depression clearly has been associated with mortality in this population, the relationship between anxiety and mortality is less clear. Accordingly, we performed a series of meta-analyses to (1) examine the relationship between anxiety and mortality in patients with established CAD and (2) determine if this relationship differs in patients with stable CAD compared to those who have just had an acute coronary syndrome (ACS). Systematic literature searches identified 44 articles (total N = 30,527) evaluating the prospective relationship between anxiety and mortality in individuals with established CAD. A series of 8 adjusted and unadjusted meta-analyses were performed to examine this relationship across all patients, with sensitivity analyses completed in post-ACS and stable CAD cohorts. In unadjusted analyses, anxiety was associated with a moderate increase in mortality risk (odds ratio 1.21 per SD increase in anxiety). However, when adjusting for covariates, nearly all associations became nonsignificant. In sensitivity analyses, anxiety was associated with an increased risk of poor outcomes in the stable CAD—but not post-ACS—cohort. These analyses confirm that anxiety is associated with increased risk of mortality in patients with CAD; however, this relationship is not as strong as that of depression and may be explained partly by other clinical factors. If anxiety screening is performed, it should be performed during a period of clinical stability and should target anxiety disorders rather than anxiety symptoms alone.